(untitled) (Huellas, 2015)
In this study we present, firstly, an overview of those graduate and postgraduate programs offered by the National University of La Plata including contents related to Africa and African-America in their curricula. Secondly, we will characterize the teaching and research practices within the mentioned areas of study as well as the main activities related to them. Finally, we will present how these studies are being increasingly developed within new institutional spaces, known as Non-Curricular Chairs.